GENES UNDERLYING POSITIVE INFLUENCE OF PRENATAL ENVIRONMENTAL ENRICHMENT AND NEGATIVE INFLUENCE OF PRENATAL EARTHQUAKE SIMULATION AND CORRECTIVE INFLUENCE OF CHINESE HERBAL MEDICINE ON RAT OFFSPRING: IRF7 AND NINJ2 - Zhang, Hui; Zhang, Xiangeng; Lin, Lin; Yang, Yinqing; Deng, Tingting; Liu, Qin; Liang, Xiaoli; Wang, Miqu; Peng, Dezhong (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Prenatal environmental enrichment (EE) has been proven to positively affect but prenatal stress negatively influence the physiological and psychological processes in animals, whose trans-generational genetic mechanism remains unclearly defined. We aimed to investigate and find out key genes underlying the positive-negative effects derived from prenatal interventions. Materials and Methods: Pregnant rats were randomized into EE group (EEG), earthquake simulation group (ESG), herbal group (HG) received herbal supplements in feed after earthquake simulation, and control group (CG). Results: Light Box Defecation Test (LBDT) showed EEG offspring presented less fecal pellets than CG offspring, ESG’s more than CG’s, and HG’s less than ESG (p’s<0.05). Open-field Test (OFT) score of EEG was higher than CG offspring, of ESG’s was lower than CG’s, and HG’s higher than ESG’s. Irf7 and Ninj were screened, which were up-regulated in EEG, down-regulated in ESG (FC<0.5), and were neutralized in HG. Prenatal EE could positively promote the nervous system development, prenatal earthquake simulation could retard the nervous system development and Chinese herbal remedy (JKSQW) which could correct the retardation. Conclusion: The negative-positive prenatal effect could contribute to altered gene expression of Irf7 and Ninj2 which also could play a key role in the improving function of JKSQW for the kidneys.